Evolutionary divergence in freshwater insects with contrasting dispersal capacity across a sea of desert. (August 2017) - Razeng, Emma; Smith, Amy E.; Harrisson, Katherine A.; Pavlova, Alexandra; Nguyen, Thuy; Pinder, Adrian; Suter, Phil; Webb, Jeff; Gardner, Michael G.; Brim Box, Jayne; Thompson, Ross; Davis, Jenny; et al.
Summary: Arid landscapes pose arguably one of the greatest challenges to dispersal of aquatic insects, and may drive speciation in taxa with low dispersal potential. We investigated genetic divergence in aquatic insects with high and low dispersal potential between two regions within the Australian arid zone. We used two dragonfly species to infer patterns for strong‐dispersing species, and mayfly species from two genera to represent weak‐dispersing species. Based on dispersal‐related traits of the taxa, we predicted that dragonflies would show little divergence between and within the two geographical regions, while mayflies would show evidence of genetic isolation, with divergence timing associated with aridification in Australia. Samples were collected from perennial pools in ephemeral stream networks in central and western Australia. The two study regions are separated by approximately 1, 500 km of predominantly dune desert. Collected insects were sequenced for one mitochondrial and one nuclear marker. We investigated spatial distribution of haplotypes, estimated divergence dates for identified mayfly lineages, and performed phylogenetic reconstruction to investigate relationships with known congeners. Both dragonfly species showed evidence of recent or ongoing gene flow between the central and western Australian study regions. In contrast, mayflies showed evidence of ancient, but not recent, gene flow between regions, with species‐level CO1 divergence within regions. We found 11 previously unknown putative mayfly species, that if confirmed could double the known diversity within these genera in Australia. Timing of divergence events for mayflies coincided with the development of the Australian arid zone, and phylogenetic relationships are similar to divergence patterns found in other Australian arid taxa. The findings of this study suggest that aridification is more likely to be a driver of diversification in taxa with low dispersal potential than in those with high dispersal potential. This is because effective aerial dispersal is integral for maintaining gene flow when aquatic connections are lost between distant populations, and reduced gene flow can promote genetic divergence.